XIAP promotes metastasis of bladder cancer cells by ubiquitylating YTHDC1 - Ning Sun; Sijia Wang; Jianting Liu; Peipei Zhang; Yixin Chang; Hongyan Li; Kun Zhao; Yijie Liu; Mingzhi Huang; Yan Hu; Zhenni Lin; Yongyong Lu; et al. (Cell Death and Disease)
Abstract X-linked inhibitor of apoptosis protein (XIAP), a member of the IAP family, is overexpressed in a variety of tumors and plays an important role in tumor progression. Increasing evidence suggests that XIAP promotes metastasis of bladder cancer but the underlying mechanism is not very clear. The RNA N6-methyladenosine (m6A) reader YTHDC1 regulates RNA splicing, nuclear transport, and mRNA stability and is a potential tumor target; however, its ubiquitin E3 ligase has not been described. In this study, screening of proteins that specifically interact with XIAP identified YTHDC1 as its degradation substrate. Ectopic overexpression of XIAP promoted degradation of YTHDC1, and knockout of XIAP upregulated YTHDC1, which inhibited metastasis of bladder cancer. Furthermore, YTHDC1 reduced the expression of matrix metalloproteinase-2 (MMP-2) by destabilizing its mRNA. These experiments revealed that XIAP promotes ubiquitination of YTHDC1, positively regulating expression of the MMP-2 and promoting metastasis of bladder cancer. Collectively, these findings demonstrate that XIAP is a critical regulator of YTHDC1 and pinpoint the XIAP/YTHDC1/MMP-2 axis as a promising target for the treatment of bladder cancer.